Systematic review of the therapeutic use of Schwann cells in the repair of peripheral nerve injuries: Advancements from animal studies to clinical trials - Vallejo, Frederic A.; Diaz, Anthony; Errante, Emily L.; Smartz, Taylor; Khan, Aisha; Silvera, Risset; Brooks, Adriana E.; Lee, Yee-Shuan; Burks, Stephen Shelby; Levi, Allan D. (Frontiers in Cellular Neuroscience, 2022)
Objective: To systematically evaluate the literature on the therapeutic use of Schwann cells in the repair of peripheral nerve injuries. Methods: The Cochrane Library and PubMed databases were searched using terms [(“peripheral nerve injury” AND “Schwann cell” AND “regeneration”) OR (“peripheral nerve injuries”)]. Studies published from 2008-2022 were eligible for inclusion in the present study. Only studies presenting data from in-vivo investigations utilizing either Schwann cells or Schwann cell-like differentiated stem cells in the repair of peripheral nerve injuries qualified for review. Studies attempting repair of a gap of >10 mm were included. Lastly, studies needed to have some measure of quantifiable regenerative outcome data such as histomorphometry, immunohistochemical, electrophysiology, or other functional outcomes. Results: A search of the PubMed and Cochrane databases revealed 322 studies. After screening using the abstracts and methods, nineteen studies were found to meet our inclusion criteria. Among the qualifying studies, twelve studies included Schwann cell transplantation and seven studies utilized pluripotent cells which had been differentiated into SC-like phenotypes prior to transplantation. Improvement in morphological and functional outcomes with the use of Schwann cells or SC-like cells in long gap peripheral nerve injuries was observed in nearly all studies. Conclusion: Based on contemporary literature, SCs have demonstrated clear potential in the repair of peripheral nerve injury in animal studies. It has yet to be determined which nerve conduit will prove superior in the facilitation of nerve regeneration. Recent developments in isolation and culturing techniques will enable further translational utilization of SCs in future clinical trials.